2016
DOI: 10.4236/ojog.2016.64028
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Sexual Behaviour with Risk of Sexually Transmissible Infection (STI) among Students in Africa: The Case of the University of Ouagadougou

Abstract: Objective: To study the sexual risk behaviors and their determining role in sexually transmissible infection (STI) and HIV among students of the University of Ouagadougou. Methodology: It was a descriptive and analytical single pass cross-sectional study from June 22 to July 21 2010 at the University of Ouagadougou. A cluster sampling in two stages was adopted to form a population of 762. Data were collected using a standardized written questionnaire completed by individual interview after informed consent. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
2
2
0
Order By: Relevance
“…There have been reports of women initiating sex earlier than their male age-mates 25 ; this was not a finding in this study, where men reported earlier sexual debut than women. The mean age of sexual debut was 18.4 years supporting findings from other studies in Tanzania and studies conducted among University students in Eastern and Western Africa that have shown that the age at sexual debut has increased over time in SSA 18 – 20 , 25 , 28 , 29 . Being in a position to attain higher level education may be protective in a way that these students have been exposed to a number of SRH classes on the importance of delaying sex and unwanted pregnancies during secondary school years, but also being under parent/teacher supervision they have restricted time for sexual relations.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…There have been reports of women initiating sex earlier than their male age-mates 25 ; this was not a finding in this study, where men reported earlier sexual debut than women. The mean age of sexual debut was 18.4 years supporting findings from other studies in Tanzania and studies conducted among University students in Eastern and Western Africa that have shown that the age at sexual debut has increased over time in SSA 18 – 20 , 25 , 28 , 29 . Being in a position to attain higher level education may be protective in a way that these students have been exposed to a number of SRH classes on the importance of delaying sex and unwanted pregnancies during secondary school years, but also being under parent/teacher supervision they have restricted time for sexual relations.…”
Section: Discussionsupporting
confidence: 85%
“…In West Africa, Ouedraogo et. al reported the prevalence of forced sex to be 11.9% by a partner 28 . Students reporting forced sex with a regular partner could probably be those engaging in transactional or cross-generational sex.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported on females initiating sex earlier than their male age-mates 26 ; this was not a finding in this study, where men reported earlier sexual debut than women. The mean age of sexual debut was 18.4 years supporting findings from other studies in Tanzania and studies conducted among University students in Eastern and Western Africa that have shown that the age at sexual debut has increased over time in SSA [18][19][20][26][27][28] .…”
Section: Discussionsupporting
confidence: 77%
“…In West Africa, Ouedraogo et. al reported the prevalence of forced sex to be 11.9% by a partner 27 . Students reporting forced sex with a regular partner could probably be those engaging in transactional or cross-generational sex.…”
Section: Discussionmentioning
confidence: 99%